Picea abies subsp. obovata (Ledeb.) Domin v slovenskih gozdovih - Šercelj, Alojz (Hladnikia (Ljubljana), 1995)
On the basis of pollen analyse and the comparison of cone scales the authors indicate the presence of Siberian spruce (Picea abies subsp. obovata) in some spruce forests in Slovenia.
Keywords: paleontologija; paleontology; pelodna analiza; sibirska smreka; Slovenia; Slovenija